The Dialectical Imagination : a History of the Frankfurt School and the Institute of Social Research, 1923-1950 - Jay, Martin (University of California Press, 1996)
Herbert Marcuse, Erich Fromm, Max Horkheimer, Franz Neumann, Theodor Adorno, Leo Lowenthal--the impact of the Frankfurt School on the sociological, political, and cultural thought of the twentieth century has been profound. The Dialectical Imagination is a major history of this monumental cultural and intellectual enterprise during its early years in Germany and in the United States. Martin Jay has provided a substantial new preface for this edition, in which he reflects on the continuing relevance of the work of the Frankfurt School.